Indonesia high school teacher's organizational citizenship behavior - Rahmania Utari (Jurnal Penelitian Ilmu Pendidikan, 2023)
The teacher's job characteristics are pretty challenging. It is widely known that teachers need extra commitment and work beyond their duties. This research aims to describe the OCB level among teachers in the Special Province of Yogyakarta, Indonesia. The study was conducted using quantitative research with a descriptive analysis technique. 97 high school teachers were involved in the study. The questionnaire employs a rating scale with a Likert scale style. The instrument of the OCB scale is developed based on the modification of the grounded research conducted by Shaheen et al. in 2016. The results show that the average score of OCB teachers attain is 80.32. There, 17.52% of teachers had a total score under 75, and 8.25% obtained a score higher than 90. Teaching etiquette and showing empathy are the most OCB performed by teachers, followed by the teacher's approach to students.  Even though the general scores in each OCB factor are pretty good, it can be found that the most suffering dimension of a teacher's OCB is in the teacher's social awareness. Tingkat perilaku kewargaan organisasi pada guru sekolah menengah atasKarakteristik pekerjaan guru terbilang menantang. Diketahui secara luas bahwa guru membutuhkan komitmen ekstra dan bekerja di luar tugasnya. Penelitian ini bertujuan untuk mendeskripsikan tingkat OCB pada guru di Provinsi Daerah Istimewa Yogyakarta, Indonesia. Metode penelitian ini adalah kuantitatif dengan teknik deskriptif. Sejumlah 97 guru SMA dilibatkan dalam penelitian ini. Kuesioner menggunakan skala penilaian dengan gaya skala Likert. Instrumen skala OCB dikembangkan berdasarkan modifikasi grounded research yang dilakukan oleh Shaheen et.al pada tahun 2016. Hasil penelitian menunjukkan rata-rata skor OCB yang dicapai guru adalah 80,32. Terdapat 17,52% guru dengan nilai total di bawah 75 dan 8,25% di antaranya memperoleh nilai total di atas 90. Etika mengajar dan menunjukkan empati merupakan OCB yang paling banyak dilakukan oleh guru, disusul dengan pendekatan individual guru kepada siswa. Walaupun skor umum pada masing-masing faktor OCB cukup baik, namun dapat ditemukan bahwa dimensi OCB guru yang paling lemah adalah kesadaran sosial guru.